Comparative evaluation of Intrathecal Fentanyl with different doses of Bupivacaine on lower limb surgery - Sharan, Radhe; Jarewal, Vishal; Singh, Harjeet; Pal Attri, Joginder (International Journal of Medical Research and Review, 2018)
Introduction: Intrathecal administration of opioids and local anaesthetics provides good analgesia. Fentanyl potentiates the afferent surgical blockade and improves both intra and post operative analgesia. The synergism between intrathecal opioids and local anaestheticsachieves a reliable spinal anaesthesia with minimal hypotension. The optimal doses and dilutions of intrathecal combination of bupivacaine and fentanyl remain a subject of discussion. Therefore, we designed this study to compare the effects of different doses of hyperbaric bupivacaine 0.5% (10 mg, 12.5 mg, 15 mg) with fentanyl 25 microgram in subarachnoid block on quality of anaesthesia and recovery. Objectives: To observe sensory and motor blockcharacteristics and effects of different doses of bupivacaine on haemodynamic parameters. Method: A prospective randomized study was carried out on three groups of 20 each. Group A patients were given 0.5% hyperbaric bupivacaine 10 mg, fentanyl 25 µg and 0.9% normal saline 1.5 ml. Group B patients were given with 0.5% hyperbaric bupivacaine 12.5 mg, fentanyl 25 µg and 0.9% normal saline 1ml. Group C patients were given 0.5% hyperbaric bupivacaine 15 mg, fentanyl 25 µg and 0.9% normal saline 0.5 ml. Results: Duration of sensory block was prolonged in group C (139.50±16.05 minutes) than group A (129.00±18.32 minutes). On statistical comparison, group B and C (126.25±15.29 minutes and 132.75±10.70 minutes respectively) had significant prolonged duration of motor block than group A (114.00±18.11 minutes). Conclusion: Fentanyl 25µg with 0.5% hyperbaric bupivacaine 12.5 mg is superior in terms of characteristics of sensory and motor block and haemodynamic stability.